B4C reinforced NiTi‐based composites: Microstructure and wear performance. Issue 3 (7th December 2022) - Velayatipour, Omid; Nikzad, Leila; Farvizi, Mohammad
Abstract: In this study, NiTi– x  wt.% B4 C ( x  = 0, 2, and 4) composites were consolidated with spark plasma sintering method, and the effects of boron carbide reinforcement addition on the microstructure and wear behavior of samples were investigated. Identification of the constituent phases of samples by the X‐ray diffraction method plus Rietveld analysis revealed that the stability of the martensite phase increased in the composite samples because of mismatch stresses between the NiTi matrix phase and the reinforcing particles, which increases the density of the dislocations and facilitates the diffusion process that subsequently leads to the formation of stable intermetallics. The results of hardness test indicated that the hardness value increased from 3.67 GPa for pure NiTi to 10.99 GPa for NiTi–4 wt.% B4 C. Results of wear test revealed that boron carbide reinforced composite specimens had higher wear resistance, whereas wear rate of NiTi sample was 3.6 × 10 −3  mm 3 /N m, and it reached to .21 × 10 −3  mm 3 /N m for NiTi–4 wt.% B4 C. Investigation of microstructure by scanning electron microscopy images and EDS analysis revealed that the wear mechanism in NiTi samples was abrasive and the addition of B4 C to NiTi changed the wear mechanisms from abrasive to a combination of oxidation, adhesive, and delamination mechanisms.